Modelo para la implementación de las TIC de una red de valor en PyME del sector Plásticos Bogotá Colombia (2018)
Through this research, we seek to present a possible solution to the low level of implementation of ICT within the value network of an SME in the plastics sector, through the development of a model built based on information collected from primary and secondary sources of information. The sources of secondary information within the project can be denoted in the development of the state of the art, where the level of progress of the implementation of technologies of the value chain could be known. Afterwards, the value chain of an SME in the plastic sector was identified and it was diagrammed by the use of VSM and SIPOC tools, knowing the processes and flows of information and resources that are involved in this value chain.